Implementasi Sensor Pir dan Kamera untuk Keamanan Ruangan Berbasis Internet of Things - Rouhillah; Inzar Salfikar; Fajri Aqsalmi (J-Innovation, 2023)
Room security is a very important thing to prioritize. One of the solutions to prevent crime levels needs to be equipped with a security device or a device capable of monitoring a room with the ability to detect the presence of an unwanted person. Therefore, this study designed a tool to monitor rooms based on the Internet of Thing (IoT) with surveillance cameras, which is one way to monitor the situation in a room. This system combines the use of the pir sensor, the raspberry pi camera module, and the raspberry pi, in order to be able to find out the condition of the room in the form of photos sent and also use bot features on internet applications, namely telegram messenger. This system is more efficient because it uses storage from telegram, and also the system will send notifications via telegram bots. So that the user can take action as soon as possible if things happen that are not desired. When the pir sensor detects movement in the room, the camera takes a photo and then sends it to the user's telegram bot account and the buzzer sounds as an early prevention of crime.